Learning Independence of Students at Dayah Muslim School in North Aceh - Zulfikar Ali Buto; Hafifuddin Hafifuddin (Budapest International Research and Critics University, 2018)
Learning independence of students at Dayah muslim school in North Aceh through various activities of Dayah in an effort to make Dayah's Alumni who are ready to adapt and continue life in society. Various activities carried out are structured, so the control and evaluation are carried out periodically. The independence of Dayah's student in the present context will experience difficulties when the necessary of the times keep developing. If the student are not ready, they will experience being overwhelmed to face global competition. This research aims to find out and describe the learning process of the independence of Islamic boarding students, especially those in the North Aceh area. This research uses a qualitative research approach with with a phenomenological approach that is descriptively qualitative. The results show student education of Islamic boarding school in North Aceh can be described through several fields, such as students' independence in doing ubuduyah, students' independence education in recitation activities, independence education in carrying out social activities, students' independence education in developing economy through another skill.